Patton's first victory : how General George Patton turned the tide in North Africa and defeated the Afrika Korps at El Guettar /: how General George Patton turned the tide in North Africa and defeated the Afrika Korps at El Guettar. (2017) - Barron, Leo; Leo Barron
No abstract available